2022
DOI: 10.1007/s00429-021-02449-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of orexin input to dopamine neurons of the ventral tegmental area projecting to the medial prefrontal cortex and shell of nucleus accumbens

Abstract: Orexin neurons are involved in homeostatic regulatory processes, including arousal and feeding, and provide a major input from the hypothalamus to the ventral tegmental area (VTA) of the midbrain. VTA neurons are a central hub processing reward and motivation and target the medial prefrontal cortex (mPFC) and the shell part of nucleus accumbens (NAcs). We investigated whether subpopulations of dopamine (DA) neurons in the VTA projecting either to the mPFC or the medial division of shell part of nucleus accumbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Conversely, Dyn decreases firing activity in most NAc medial shell-and basolateral amygdala (BLA)-projecting dopaminergic neurons and in a small part of the NAc lateral shell-projecting dopaminergic neurons in the VTA [117]. Furthermore, LH orexin neurons also project to some mPFCprojecting dopaminergic neurons in the VTA [118]. The optogenetic activation of the inputs from the LH orexin and Dyn neurons to the VTA enhances dopamine release in the NAc core, promoting reward-seeking behaviors.…”
Section: Orexin and Dynorphinmentioning
confidence: 99%
“…Conversely, Dyn decreases firing activity in most NAc medial shell-and basolateral amygdala (BLA)-projecting dopaminergic neurons and in a small part of the NAc lateral shell-projecting dopaminergic neurons in the VTA [117]. Furthermore, LH orexin neurons also project to some mPFCprojecting dopaminergic neurons in the VTA [118]. The optogenetic activation of the inputs from the LH orexin and Dyn neurons to the VTA enhances dopamine release in the NAc core, promoting reward-seeking behaviors.…”
Section: Orexin and Dynorphinmentioning
confidence: 99%
“…The ORX regulates arousal and wakefulness through modulation of the locus coeruleus 8 . Various studies on experimental animals have shown that the neuropeptide ORX is involved in locomotor activity, attention, cognition, feeding behavior reward, and thermogenesis by regulating prolactin, growth hormones, acetylcholine, and corticosterone levels [8][9][10][11][12] . Liguori et al demonstrated an increase in CSF ORX levels in patients with moderate to severe AD was associated with sleep dysfunction and decline in cognition 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their location in wake-controlling regions of the brain, OXRs are found in areas of the mesolimbic dopamine system ( Cole et al, 2020 ; Kallo et al, 2022 ; Kawashima et al, 2022 ; Schmeichel et al, 2017 ) where they help to orchestrate the amount of arousal necessary for successfully engaging in highly motivational and rewarding tasks ( de Lecea, 2021 ). For example, in rats, OXR signaling mediates natural or drug-related reward seeking under large effort requirements ( Schmeichel et al, 2018 ) and is required to make cognitive associations of the environmental context to reward reception ( Harris et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%